Online Database Load Balancer to Collaborating With Existing Database - Chavan, Megha; Pawar, Shital; Shaikh, Sadiya; Wadagave, Priyanka; Tambat, Deepika (International Journal of Computer Sciences and Engineering, 2025)
According to literature meaning of Cloud Computing is distributed computing, storing, sharing, and accessing data over the internet. Cloud is the platform which provides numerous type of resources where the end user may use the resource for developing own software and even their own cloud and even include a new resource to the existing once. The biggest issue for a cloud datacentre is to tackle with billions of request coming dynamically from the end users to handle their database in efficient and effective manner. To achieve this goal, various load balancing approaches have been proposed in past years. Database load balancing strategies aim at achieving high software developer satisfaction by producing service like auto scale of their data in database, zero-downtime, multiple database choices, multi tenancy support. Load balancing in this environment means equal distribution of workload across instances. End users needs ample space to store their database data to decrease the maintenance cost and buying cost of servers and area required to assemble them this paper focus on the balancing the data in database. This paper, focus on database based load balancing which works well in cloud environment, considers resources specific demands of the tasks and reduces overflow of data overhead by dividing the data on running instances.